2000
DOI: 10.1007/s12110-000-1014-2
|View full text |Cite
|
Sign up to set email alerts
|

Is human conversation more efficient than chimpanzee grooming?

Abstract: Clique sizes for chimpanzee (Pan troglodytes) grooming and for human conversation are compared in order to test Robin Dunbar's hypothesis that human language is almost three times as efficient a bonding mechanism as primate grooming. Recalculation of the data provided by Dunbar et al. (1995) reveals that the average clique size for human conversation is 2.72 whereas that of chimpanzee grooming is shown to be 2.18. The efficiency of human conversation and actual chimpanzee grooming over Dunbar's primate groomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…less time-consuming, way of investing in social relationships, as originally postulated by Dunbar (1993). In line with this, Nakamura (2000) found that grooming cliques among chimpanzees were similar in size to human conversation cliques, i.e. in principle providing the same bonding efficiency.…”
Section: Discussionsupporting
confidence: 70%
“…less time-consuming, way of investing in social relationships, as originally postulated by Dunbar (1993). In line with this, Nakamura (2000) found that grooming cliques among chimpanzees were similar in size to human conversation cliques, i.e. in principle providing the same bonding efficiency.…”
Section: Discussionsupporting
confidence: 70%
“…Both authors are well accustomed to the behavior patterns of Mahale chimpanzees, as M.N. has studied Mahale chimpanzees, focusing mostly on social behavior (Nakamura 2000(Nakamura , 2003b, for an accumulated total of more than 2 years and T.N. has studied them for 11 years.…”
Section: Methodsmentioning
confidence: 99%
“…Such an interpretation might be extended to bi‐directional grooming in those species where bi‐directional grooming is common (e.g. chimpanzees and, to a lesser extent, gelada baboons: Nakamura 2000; R. Dunbar, pers. obs.…”
Section: Introductionmentioning
confidence: 99%